Perception of Visible Tattoos in Employment and Career Development: Evidence from Hungarian Labour Market - Karácsony, Péter; Valkó, Vivien; Reichel, Blanka; Gaál, Krisztina Károlyi (Journal of Ecohumanism, 2024)
In this study, the perception of tattooed employees is examined, focusing on their employment and career development opportunities. The perception of tattoos in employment and career development is a complex and changing issue that depends on many factors. Some industries and workplaces may be stricter about tattoos, while other workplaces are more tolerant and accepting. The method of the research is primary research, including a questionnaire survey, which presents the subject under research in relation to the Hungarian labour market. The hypothesis test revealed that a statistical correlation between the visibility of tattoos and the type of employment (white-collar or blue-collar) can be demonstrated, and that visible tattoos also have an impact on an individual's career development. These results support that the perception of tattoos can vary in employment and career development, individual circumstances, the applied employment policy, and the specific workplace culture can significantly influence this process. It is important that employees, thinking about the future and labour market opportunities, make a decision that supports the creation of a balance between tattoos and career.